Effects of Gender and Recurrent Low Back Pain on Lifting Style - Ram Haddas; Philip Sizer; James Yang (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
Objective: The purpose of this study was to examine the influence of gender and existing, recurrent low back pain (rLBP) on lower extremity and trunk mechanics, as well as neuromuscular control, during a lift task. Design: A multivariate design was used to examine the effects of gender and group on biomechanical and neuromuscular control variables in randomized symmetric and asymmetric lifting. Methods: 68 Males and females with rLBP and healthy performed symmetric and asymmetric weighted box lifting trials to a 1 meter height table. Results: Lifting style was different between gender and between the rLBP versus healthy groups during a 1m box lifting. A significant two-way interaction effect between gender and group was observed for multifidus muscle activity and knee rotation in asymmetric lifting. Several gender and group main effects were observed in pelvis obliquity, trunk flexion and side flexion, knee abduction angles in symmetric lifting; and in pelvis obliquity and rotation, trunk flexion and side flexion, hip abduction, knee abduction angles, external oblique and internal oblique muscles activity in asymmetric lifting. Conclusions: Females and individuals with rLBP appear to use different lifting styles that emphasize movement at the pelvis accompanied by poor kinematic control features at the hip, trunk and knee. Clinicians should be mindful of these changes when developing prevention and rehabilitation programs aimed at improving trunk control in preparation for lifting tasks during domestic and occupational activities.